MANAGEMENT OF SPECIAL RADIOACTIVE WASTES: PRACTICAL ADVANCES AND CURRENT CHALLENGES - I. I. Linge; M. N. Savkin; M. V. Vedernikova (Радиационная гигиена)
The article covers methodological approaches for substantiating the assignment of radioactive wastes (RAO) to special radioactive wastes, as well as the results of its practical application within initial registration of RAO.